Fitting Aktual Kacamata Plastik Full Frame Berdasarkan Kenyamanan Pasien Optik Pranoto Madiun - Dwi Oktyana; Adi Cahyono; Joko Sulistyo (STIKES HAKLI Semarang, 2024)
Fitting on the frame is the process of fitting on the glasses that aims to set the symmetry of the frame to the user glasses so that the user’s glasses fell comfortable when ewaring glasses. The purpose of this study is to know the process of fitting in Optical Pranoto of Madiun and to do actual fitting techniquebased on patient’s comfort. This research is a descriptive casa of “Actual Fitting on Eyeglasses with Full Frame Plastic Frame Based on Patient Comfort at Optical Pranoto Branch of Madiun”. This research was conducted by using the method of direct observation of the patien’s complaints. Survey result at Optical Pranoto branch Madiun during the period of October-November 2022 on the actual distribution of glasses fittings and various types of frame in the process of fitting. The author focus on taking the data frame of full frame plastic that amounted to 56 people. The reason the author retrieve the data frame full frame plastic because there is often a complaint of asymmetry between the two pemple so as to make the patient uncomfortable when using glasses. The fitting process in Optical Pranoto branch Madiun first do standard fitting and then done the actual fitting process. Comfort when wearing glasses is not only focused on giving the size of the dioptri but also in the process of fitting the glasses in accordance whit the comfort of the patient.